Avaliação das práticas de controle de contaminação cruzada em domicílios de celíacos - TAVARES, Géssica Fortes (2023)
Background: A glutenfree diet requires special attention due to the risks of cross contamination, since small amounts of gluten can trigger signs and symptoms and impair the health and quality of life of celiac patients. Implementing good practices to promote the safe environment with glutenfree people in glutenshared homes is critical to ensuring a safe home environment. Objective: To evaluate crosscontamination control practices in celiac households. Methods: Crosssectional and analytical procedure study, with nonprobabilistic sampling made by a virtual questionnaire, which evaluated the knowledge of celiac disease, and a crosscontamination, and some practices that prevent the gluten contamination. To analyze estatistically, the Spearman correlation test was used, with 5% of significance. Results: 98.63% of the individuals study and research about celiac disease, 97.26% know what is cross contamination by gluten; 87.67% of them reported suspecting having suffered cross contamination. As for the evaluation of crosscontamination control practices, of the 12 items presented, 5 showed a hit percentual below 50%. The action that had the lowest hit percentual was the use of commom surfaces (34%). Conclusion: There is still considerable lack of practice in controlling crosscontamination, which can impact negatively the treatment and life quality of celiacs.